Social Business: A Revolutionary Idea in the Field of Poverty Alleviation - Hoque, Sayema (IIUC Studies, 2014)
Poverty is one of the major problems around the world. Prof. Dr. Muhammad Yunus has come up with a revolutionary idea to solve that problem by introducing the social business concept which emphasizes a combined and organized effort of poverty alleviation through self-sustaining business mechanism. This paper attempts to overview of the idea, discuss current practice of social business in Bangladesh; and compare social business model with other existing business models. DOI: http://dx.doi.org/10.3329/iiucs.v8i0.20404 IIUC Studies Vol.8 December 2011: 81-94